Nano- and Macroscale Imaging of Cholesterol Linoleate and Human Beta Defensin 2-Induced Changes in Pseudomonas aeruginosa Biofilms - Brent A. Beadell; Andy Chieng; Kevin R. Parducho; Zhipeng Dai; Sam On Ho; Gary Fujii; Yixian Wang; Edith Porter (MDPI AG, 2021)
The biofilm production of Pseudomonas aeruginosa (PA) is central to establishing chronic infection in the airways in cystic fibrosis. Epithelial cells secrete an array of innate immune factors, including antimicrobial proteins and lipids, such as human beta defensin 2 (HBD2) and cholesteryl lineolate (CL), respectively, to combat colonization by pathogens. We have recently shown that HBD2 inhibits biofilm production by PA, possibly linked to interference with the transport of biofilm precursors. Considering that both HBD2 and CL are increased in airway fluids during infection, we hypothesized that CL synergizes with HBD2 in biofilm inhibition. CL was formulated in phospholipid-based liposomes (CL-PL). As measured by atomic force microscopy of single bacteria, CL-PL alone and in combination with HBD2 significantly increased bacterial surface roughness. Additionally, extracellular structures emanated from untreated bacterial cells, but not from cells treated with CL-PL and HBD2 alone and in combination. Crystal violet staining of the biofilm revealed that CL-PL combined with HBD2 effected a significant decrease of biofilm mass and increased the number of larger biofilm particles consistent with altered cohesion of formed biofilms. These data suggest that CL and HBD2 affect PA biofilm formation at the single cell and community-wide level and that the community-wide effects of CL are enhanced by HBD2. This research may inform future novel treatments for recalcitrant infections in the airways of CF patients.